On almost (N,p,q) summability of conjugate Fourier series - Shyam Lal; Hare Krishna Nigam (International Journal of Mathematics and Mathematical Sciences)
A new theorem on almost generalized Nörlund summability of conjugate series of Fourier series has been established under a very general condition.